2004
DOI: 10.1145/1024074.1024075
|View full text |Cite
|
Sign up to set email alerts
|

ProtoMol, an object-oriented framework for prototyping novel algorithms for molecular dynamics

Abstract: ProtoMol is a high-performance framework in C++ for rapid prototyping of novel algorithms for molecular dynamics and related applications. Its flexibility is achieved primarily through the use of inheritance and design patterns (object-oriented programming). Performance is obtained by using templates that enable generation of efficient code for sections critical to performance (generic programming). The framework encapsulates important optimizations that can be used by developers, such as parallelism in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 32 publications
0
56
0
Order By: Relevance
“…This effort lead to the design of two efficient software tools facilitating the process of setting up an IMS : NAMD and VMD [Phillips et al (2005)] [Nelson et al (1995))]. The underlying exchange protocol is also supported by ProtoMol [Matthey et al (2004)], LAMMPS [Plimpton (1995)], HOOMD-blue [Anderson et al (2008)] and any software using the MDDriver library [Delalande et al (2009)]. Similar projects proposing an interactive display for molecular simulations exist, such as the Java3D interface proposed in Knoll & Mirzaei (2003) and Vormoor (2001), or the Protein Interactive Theater [Prins et al (1999)].…”
Section: Introductionmentioning
confidence: 99%
“…This effort lead to the design of two efficient software tools facilitating the process of setting up an IMS : NAMD and VMD [Phillips et al (2005)] [Nelson et al (1995))]. The underlying exchange protocol is also supported by ProtoMol [Matthey et al (2004)], LAMMPS [Plimpton (1995)], HOOMD-blue [Anderson et al (2008)] and any software using the MDDriver library [Delalande et al (2009)]. Similar projects proposing an interactive display for molecular simulations exist, such as the Java3D interface proposed in Knoll & Mirzaei (2003) and Vormoor (2001), or the Protein Interactive Theater [Prins et al (1999)].…”
Section: Introductionmentioning
confidence: 99%
“…8 Another example is the ProtoMol framework, which was designed especially for computational experimentation and so has well-defined partitions among computations. 9 We have found that the acceleratable kernel not only comprises more than 90 percent of execution time with ProtoMol, but the modularity enables straightforward integration of an FPGA accelerator. 10 …”
Section: Methods 4: Living With Amdahl's Lawmentioning
confidence: 95%
“…A C + + implementation of S2HMC is provided in the program PROTOMOL 2.1. 13 Here we use a Python implementation for easier understanding. The reader interested in implementation details will find them in this section and can safely skip the next two sections.…”
Section: Separable Shadow Hybrid Monte Carlomentioning
confidence: 99%
“…Tests were performed with the open-source simulator PROTOMOL, 13 which uses the CHARMM 22 force field. 22,23 We tested the method using five boxes of flexible TIP3P ͑Ref.…”
Section: Numerical Testsmentioning
confidence: 99%